Strategies of Islamic Education Teachers to Increase Students’ Interest In Learning and Practicing in State Junior High School Lanrisang (SMPN) 1 Lanrisang, Pinrang - Das, St.Wardah Hanafie; Halik, Abdul; Zulfianah, Zulfianah; Naim, Muh (Madania: Jurnal Kajian Keislaman, 2018)
This study aims to examine strategies used by Islamic education teachers to increase learning interest and practice of Islamic education on students of SMPN 1 Lanrisang, Pinrang. Increasing interest to study and practice Islamic education course on public school’s students is important for academics and practitioners. Therefore, a proper design of learning strategies is needed to increase interest and practice of the course. This article employed a qualitative method with a phenomenological approach by looking at the phenomena in the field. The results of interview and data analysis show some factors causing students’ low interest in learning Islamic education, including students’ low awareness during the learning activity, memorization system and indoctrination, tight schedule, national exam, a monotone learning strategy, and lack of family support. In addition, students seldom perform worship of mahdhah, while they often perform mu’âmalah. To increase the learning interest, the teachers of SMPN 1 Lanrisang used specific learning strategies such as lecture, debate, role-play, simulation, demonstration, contextual-based, problem-based, habituation and togetherness.